2009
DOI: 10.1007/s00424-009-0733-4
|View full text |Cite
|
Sign up to set email alerts
|

Anionic phospholipids differentially regulate the epithelial sodium channel (ENaC) by interacting with α, β, and γ ENaC subunits

Abstract: Anionic phospholipids (APs) present a variety of lipids in the cytoplasmic leaflet of the plasma membrane, including phosphatidylinositol (PI), PI-4-phosphate (PI(4) P), phosphatidylserine (PS), PI-4,5-bisphosphate (PI(4,5) P 2 ), PI-3,4,5-trisphosphate (PI(3,4,5)P 3 ), and phosphatidic acid (PA). We previously showed that PI(4,5)P 2 and PI(3,4,5)P 3 upregulate the renal epithelial sodium channel (ENaC). Further studies from others suggested that PI(4,5) P 2 and PI(3,4,5)P 3 respectively target β-and γ-ENaC su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…We have shown that anionic phospholipids including PIP 2 can bind to all three ENaC subunits and directly stimulate ENaC in distal nephron A6 cells [18,19]. Recently, we have also shown that PIP 2 is predominantly located in microvilli and that PIP 2 distribution between microvilli and non-microvillar planar region depends on Cho synthesis in the CCD cells [13].…”
Section: Introductionmentioning
confidence: 95%
“…We have shown that anionic phospholipids including PIP 2 can bind to all three ENaC subunits and directly stimulate ENaC in distal nephron A6 cells [18,19]. Recently, we have also shown that PIP 2 is predominantly located in microvilli and that PIP 2 distribution between microvilli and non-microvillar planar region depends on Cho synthesis in the CCD cells [13].…”
Section: Introductionmentioning
confidence: 95%
“…Tryptophan fluorescence anisotropy represents the ordering of the hydrophobic Trp environment. Fluorescence anisotropy of Trp 31 did not change in the presence of any lipid, indicating that the peptide is not incorporated into the membrane. 4 This result reiterates our observations that ␥NT acquires secondary structure in the presence of APs, with higher specificity for PIP 2 .…”
Section: A-c)mentioning
confidence: 92%
“…K-clusters in ␤-and ␥-ENaC Strongly Influence ENaC Proteolytic Regulation-Previous studies have reported direct interaction with APs of the N terminus of ␤-ENaC (␤NT) and ␥-ENaC (␥NT) (31). We therefore extended our computational analyses to study the possible structural changes induced by PIP 2 in ␤NT.…”
Section: A-c)mentioning
confidence: 99%
See 2 more Smart Citations